Control strategy to limit duty cycle impact of earthquakes on the LIGO gravitational-wave detectors. (31st January 2018) - Biscans, S; Warner, J; Mittleman, R; Buchanan, C; Coughlin, M; Evans, M; Gabbard, H; Harms, J; Lantz, B; Mukund, N; Pele, A; Pezerat, C; et al.
Abstract: Advanced gravitational-wave detectors such as the laser interferometer gravitational-wave observatories (LIGO) require an unprecedented level of isolation from the ground. When in operation, they measure motion of less than 10 −19 m. Strong teleseismic events like earthquakes disrupt the proper functioning of the detectors, and result in a loss of data. An earthquake early-warning system, as well as a prediction model, have been developed to understand the impact of earthquakes on LIGO. This paper describes a control strategy to use this early-warning system to reduce the LIGO downtime by ̃30%. It also presents a plan to implement this new earthquake configuration in the LIGO automation system.